Effect of Feed Depth on the ProcessMilling Against Surface Roughness Steel 4140 Carbide Endmill Applications - Suhardi Napid; Ahmad Bakhori (International Journal of Health Engineering and Technology, 2024)
In the metal cutting industry today, milling process applications are still carried out using cutting fluids. One of the criteria for determining machining quality is surface roughness. Surface roughness as a dependent variable is influenced by machining parameters, namely feed depth, cutting speed and feed speed as independent variables. Research activities with the aim of obtaining machined surface roughness of 4140 low alloy steel workpieces due to spindle rotation speed and feed depth using carbide endmill cutting tools. Research activities were carried out with 9 specimens for the vertical milling process using cutting fluid through variations in machine spindle rotation of 1200 rpm, 1400 rpm and 1600 rpm and feed depths of 0.5 mm, 0.75 mm, 1 mm. Data processing was carried out using experimental methods to obtain surface roughness data.